Ecological processes and biogeochemical cycling in salt marshes: synthesis of studies in the Bahía Blanca estuary (Argentina) - Negrin, Vanesa Lorena (2016)
Here we offer an integrative review of biogeochemical cycling of carbon, nitrogen, phosphorus, and several metals in salt marshes of the Bahía Blanca Estuary, located in South America, which is a region underrepresented in the literature. The dominant species, Spartina alterniflora and Sarcocornia perennis, have low net aboveground primary productivity but play substantial and contrasting roles in the biogeochemical cycling of elements. S. perennis was more efficient at metal sequestration, whereas S. alterniflora was important in the immobilization of phosphorus. Because of the differences in net aboveground primary productivity between high and low marsh, plant position should be considered to evaluate the role of S. alterniflora on biogeochemical cycles. Some elements were also in high concentrations in belowground tissues but, based on our data, we could not accurately estimate net belowground primary productivity, a key process to evaluate elemental cycling in salt marshes. In spite of uncertainties in the estimations, the slower decomposition rates in S. alterniflora would be indicative of a higher contribution to the long-term storage of nutrients and metals within the marsh. Regardless shortcomings, our work represents a valuable tool for comparisons with salt marshes worldwide.